Real-Time Interactive Quizzes as Formative Assessment in Child Protection Education: A Quasi-Experimental Study - Nesna Agustriana; Siyyella Tika Nasution (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to examine the effectiveness of real-time interactive quizzes as a formative assessment instrument in enhancing Early Childhood Education Teacher Education (PGPAUD) students' understanding of child violence and rights violations. Using a one-group pretest-posttest quasi-experimental design, the study involved 25 students enrolled in the Child Protection course at Bengkulu University. Participants completed a live digital quiz consisting of multiple-choice questions covering key dimensions of child protection. The findings indicate a statistically significant improvement in students' understanding following the intervention, with a large effect size demonstrating substantial learning gains. The greatest improvement was observed in evidence-based intervention concepts, while notable gains were also found in students' understanding of economic exploitation and systemic discrimination. Most participants demonstrated improved performance, with the largest gains occurring among initially lower-performing students, consistent with Vygotsky's concept of the zone of proximal development. This study contributes to the literature by demonstrating the value of interactive quizzes as formative assessment tools in the underexplored context of PGPAUD child protection education in Indonesia and highlighting the usefulness of indicator-level diagnostic feedback for instructional decision-making. However, the findings should be interpreted with caution due to the absence of a control group and the limited sample drawn from a single institution.